2020
DOI: 10.31557/apjcp.2020.21.12.3579
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Toxicity of Eleutherine palmifolia (L.) Merr. Extract on BALB/c Mice Colitis-Associated Colon Cancer Model

Abstract: Objective: Eleutherine palmifolia (L.) Merr. extract (EPE) containing isoliquiritigenin and oxyresveratrol is believed to be an anticancer agent. This study evaluates colon histopathology, TNF-α, TGF-β, and hepatotoxicity on BALB/c mice colitis-associated colon cancer (CAC) model treated with EPE. Methods: In vivo study was performed on BALB/c mice CAC model induced by 10 mg/kgBW AOM on the first day followed by administration that each cycle consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Natural ingredients proven to have anticancer properties include resveratrol. [ 12 13 ] Our findings showed that resveratrol had good bioavailability and interacted with genes associated with lung cancer. Consistently, resveratrol might be involved in the biological process of lung cancer either the P53 signaling pathway (Hsa04115), MicroRNAs in cancer (Hsa05206), and Apoptosis (Hsa04210) either in small-cell lung cancer (Hsa05222) or nonsmall-cell lung cancer (Hsa05223) from network pharmacology followed by PPI network analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Natural ingredients proven to have anticancer properties include resveratrol. [ 12 13 ] Our findings showed that resveratrol had good bioavailability and interacted with genes associated with lung cancer. Consistently, resveratrol might be involved in the biological process of lung cancer either the P53 signaling pathway (Hsa04115), MicroRNAs in cancer (Hsa05206), and Apoptosis (Hsa04210) either in small-cell lung cancer (Hsa05222) or nonsmall-cell lung cancer (Hsa05223) from network pharmacology followed by PPI network analysis.…”
Section: Discussionmentioning
confidence: 84%
“…After dehydration and mounting, all slides immunostained with IL-6, TNF-α, CK20, or COX-2 antibody were examined and scored by pathologists for the percentage of cells showing specific immunostaining signals. Non-repeatable fields were selected at ×200 magnification to analyze the percentage of positively stained cells (score 1, 0–25%; score 2, 26–50%; score 3, 51–75%; score 4, 76–100%) for the final IHC score [ 70 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adding Dayak onion extract to food products influences the product's characteristics and antioxidant content. Dayak onions (Eleutherine palmifolia) are one of the plants known to have antioxidant (Febrinda et al, 2014), anti-inflammatory (Paramita & Nuryanto, 2019;Insanu et al, 2014), antibacterial (Harlita et al, 2018;Insanu et al, 2014), anti-hypertension (Rauf et al, 2018), inhibitor of -glucosidase and HIV replication (Insanu et al, 2014), and colon anticancer abilities (Mutiah et al, 2020). Dayak onions belong to the Iridaceae family and have long been used by ethnic Dayaks in Borneo as a traditional medicine for various types of diseases such as breast cancer, high blood pressure (hypertension), diabetes mellitus, cholesterol-lowering, heart disease, and stroke (Kuntorini et al, 2016).…”
Section: Anggarkasih Et Al (2023)mentioning
confidence: 99%